Vowel transitions in the Northern dialect of North accent of the Azerbaijani language and “kipchak” language elements in them - Samedova, Konul (Turkic Studies Journal, 2021)
The influence of Oghuz and Kipchak languages should be especially noted when talking about related languages. Because these languages are at the heart of the phonetics, vocabulary and grammar of the Azerbaijani dialects. Studying the history of a language and the role of intra-linguistic and extraneous influences is valuable and important enough to reveal the history of not only one language, but also of related languages close to that language. The Northern dialect of North accent of the Azerbaijani language which are vast in terms of territory, differ in the richness and diversity from other accents of the Azerbaijani language. Although there are many dialect features in this region, the dialects of the northern group combine the richness of both Oghuz and Kipchak language elements. The article identifies traces of Kipchak language features in dialectological materials collected from northern dialects, and thus the formation of Kipchak tribes in these regions is proved by linguistic facts. The article talks about the dialectological tasks of the interchangeability of sounds in the dialect (pronunciation) of the Azerbaijani language and vowel sound transitions in the dialect of the groups of the Northern dialect. This phonetic process, in contrast to the literary language, is more common in the adverb (manner of speaking, pronunciation). The study of these phonetic processes is of great importance for dialectical study (concept), as well as for the simultaneous study of the phonetics of languages, the level of their mutual integration into each other in Turkological linguistics (philology, linguistics). The article also clarifies the similarities and parallelism of the transition of vowels of the Northern dialect of the Azerbaijani language with elements of the “kipchak” language. The process of transition of the Northern dialect and their interchangeability is investigated, analyzed, studied using (based on) the table of M.Shiraliev’s groupings.